Uma história de delimitações teóricas: trinta anos de semântica no Brasil - Oliveira, Roberta Pires de (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
A map of the state of the art in semantics during the last third years of linguistics in Brazil is presented in the first section. Two case studies, then, are analysed: the debate argumentative semantics and formal semantics, and the debate formal semantics and cognitive semantics. Our analysis shows that an effective strategy for theoretical autonomy is that of declaring war to the dominant model. We do not subscribe to the war metaphor as an explanation to knowledge, however. Our paper finishes with some words on epistemology.